ifo World Economic Survey May 2018 - Dorine Boumans; Carla Krolage (ifo World Economic Survey, 2018)
World Economic Climate: ifo World Economic Climate Deteriorates - Advanced Economies: Upturn in the Advanced Economies Loses its Momentum - Emerging and Developing Economies: Recovery in Emerging Market and Developing Economies Cools Down - Special Topic: US Tax and Trade Policy – Perceived Impact and Preferred Policy Responses Worldwide
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies